2023
DOI: 10.3390/biomedicines11030713
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory Blood Signature Related to Common Psychological Comorbidity in Chronic Pain

Abstract: Chronic pain is characterized by high psychological comorbidity, and diagnoses are symptom-based due to a lack of clear pathophysiological factors and valid biomarkers. We investigate if inflammatory blood biomarker signatures are associated with pain intensity and psychological comorbidity in a mixed chronic pain population. Eighty-one patients (72% women) with chronic pain (>6 months) were included. Patient reported outcomes were collected, and blood was analyzed with the Proseek Multiplex Olink Inflammat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 88 publications
0
3
0
Order By: Relevance
“…Plasma proteomic studies of FM patients have found protein patterns correlating with psychological distress aspects ( 35 , 125 ). Also, studies using targeted panels of proteins have reported significant corelations between plasma protein patterns and anxiety and depression in a mixed group of chronic pain patients ( 145 ). We are not aware of studies investigating the relationships with health.…”
Section: Discussionmentioning
confidence: 99%
“…Plasma proteomic studies of FM patients have found protein patterns correlating with psychological distress aspects ( 35 , 125 ). Also, studies using targeted panels of proteins have reported significant corelations between plasma protein patterns and anxiety and depression in a mixed group of chronic pain patients ( 145 ). We are not aware of studies investigating the relationships with health.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, higher IL-8 levels were related to less widespread pain in chronic pelvic pain [ 48 ] and fewer depressive symptoms [ 49 ] in treatment-resistant depression in women but not in men. Moreover, in exploratory proteomics analyses, distinct networks of blood markers appear related to defined aspects of the disorder, such as pain intensity, pain sensitivity, or psychological comorbidity [ 50 , 51 ].…”
Section: Inflammation and Painmentioning
confidence: 99%
“…Pain comorbidity could represent a double-hit challenge for the CNS, as discussed above. Moreover, some studies suggest that patients experiencing both pain and mood disturbances may in fact show unique inflammatory characteristics [ 50 , 51 , 87 ]. For example, treatment-resistant depressed patients who experience pain comorbidity have higher blood IL-6 and granulocyte-macrophage colony-stimulating factor levels compared to patients without pain [ 88 ].…”
Section: Mood and Cognition Interact With Inflammation And Painmentioning
confidence: 99%